HUBUNGAN KEKUATAN OTOT LENGAN DENGAN KEMAMPUAN LEMPAR LEMBING PADA SISWA SMA NEGERI 1 PURIALA - Andriawan; Asmuddin; Badaruddin (Journal Olympic (Physical Education, Health and Sport), 2021)
The purpose of this study was to determine the relationship between arm muscle strength and the javelin throwing ability of students of SMA Negeri 1 Puriala. The formulation of the problem in this study is "is there a relationship between arm muscle strength and the javelin throwing ability of students of SMA Negeri 1 Puriala. The population in this study were 370 students of SMA Negeri 1 Puriala, consisting of 210 girls and 160 boys, the sample in this study was taken by purposive sampling technique, namely the sample was selected with the consideration of male gender as much as 20% of 160 male students. in order to obtain a sample of 32 people. The instrument used to measure the arm muscle strength test was thetest pull up for 60 seconds, while the instrument used to measure the javelin throwing ability test was the javelin throwing test which was carried out 3 times per student. The research data were analyzed using the product moment statistical technique at a significant level of 0.05. The results obtained from testing the hypothesis show that Rxy  = 0.93> r table at a significant level of 0.05 = 0.349. The value of the coefficient of detrimination of arm muscle strength with the ability to throw the javelin is 0.86 or 86%. In this study, it can be concluded that there is a significant relationship between arm muscle strength and the javelin throwing ability of the students of SMA Negeri 1 Puriala.